Discerning One Primary Purpose From Two:: The Inconsistent Treatment of Sexual Assault Nurse Examiner Testimony Under the Sixth Amendment’s Confrontation Clause - Tessa DeFranco (Columbia Journal of Gender and Law, 2025)
Survivors of sexual assault and domestic violence often play a critical role in the criminal prosecutions of their abusers. The cyclical dynamics of abuse and corresponding prevalence of factors such as trauma, intimidation, and coercion, however, mean that survivors are often unavailable or unwilling to testify at trial. In these instances, a victim’s prior outof- court statements may nonetheless be admissible if they satisfy the Sixth Amendment’s Confrontation Clause. This Note explores Confrontation Clause jurisprudence in the context of victim statements made during Sexual Assault Nurse Examiner (SANE) examinations and demonstrates how the divergent approaches taken by courts around the country have left defendants, law enforcement, SANEs, and victims without a coherent framework governing the admissibility of these statements at trial. Part I details the responsibilities of SANEs and the significant role they play in the provision of both medical care and evidentiary support in subsequent criminal prosecutions. Part II lays out the evolution of the U.S. Supreme Court’s Confrontation Clause jurisprudence, from its longstanding focus on reliability to its modern-day primary purpose analysis. Part III explicates how courts throughout the United States analyze the testimonial nature of statements made by victims of sexual assault in the context of SANE examinations. Finally, Part IV recommends solutions to create a more consistent framework for analyzing SANE testimony when a victim is unavailable come trial, including practical changes to SANE programs as well as doctrinal changes to Confrontation Clause jurisprudence. Ultimately, this Note advocates for a declarant-centered approach due to the unique nature of domestic violence and sexual assault prosecutions, including the high rate of unavailable witnesses, the vulnerability involved in a sexual assault examination, and the likelihood of re-traumatization.